All-optical azimuthal trapping of dissipative Kerr multi-solitons for relative noise suppression - Shandilya, Pradyoth; Ou, Shao-Chien; Stone, Jordan; Menyuk, Curtis; Erkintalo, Miro; Srinivasan, Kartik; Moille, Grégory (APL, 2025)
Temporal cavity solitons, or dissipative Kerr solitons (DKSs) in integrated microresonators, are essential for deployable metrology technologies. Such applications favor the lowest noise state, typically the single-DKS state where one soliton is in the resonator. Other multi-DKS states can also be reached, offering better conversion efficiency and thermal stability, potentially simplifying DKS-based technologies. Yet they exhibit more noise due to relative soliton jitter and are usually not compatible with targeted applications. We demonstrate that Kerr-induced synchronization, an all-optical trapping technique, can azimuthally pin the multi-DKS state to a common reference field. This method ensures repetition rate noise is independent of the number of solitons, making a multi-DKS state indistinguishable from a single-DKS state in that regard, akin to trapped-soliton molecule behavior. Supported by theoretical analysis and experimental demonstration in an integrated microresonator, this approach provides metrological capacity regardless of the number of cavity solitons, benefiting numerous DKS-based metrology applications.
Keywords: UMBC Computational Photonics Lab; UMBC Optical Fiber Communications Laboratory